A generalization of 4-dimensional locally conformal flat Walker manifolds - S. Azimpour; M. Chaichi; M. Toomanian (Հայաստանի ԳԱԱ)
A 4-dimensional Walker metrics with c = 0 on A semi-Riemannian manifold M have been investigated by E. Garci'a-Ri'o and Y.Matsushita. The case c=constant has been studied in [1]. In this paper we generalize these notions to the case of non-constant c. We find the form of the defining functions that makes this manifold similar to locally conformal flat 4-dimensional Walker manifold.
Keywords: Mathematics; Science